Savings banks and the industrial revolution in Prussia: Supporting regional development with public financial institutions - Sibylle H. Lehmann-Hasemeyer; Fabian Wahl (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We show that smaller, regional public financial intermediaries significantly contributed to industrial development, using a new data set of the foundation year and location of Prussian savings banks. This extends the banking-growth nexus beyond its traditional focus on the large universal banks, to savings banks. The saving banks had an impact through the financing of public infrastructure, such as railways, and new private factories. Saving banks were public financial intermediaries, so our results strongly suggest that state intervention can be very successful, particularly in regions in the early stages of industrial development when capital requirements are manageable, and access to international capital markets is limited.
urn:nbn:de:bsz:100-opus-13885
Keywords: G21; N23; N74; N93; R11; 330; Savings Banks; Prussia; Industrialisation; Public Infrastructure; Regional and Urban Development